Coming of age, becoming obese: a cross-sectional analysis of obesity among adolescents and young adults in Malaysia. (December 2016) - Pell, Christopher; Allotey, Pascale; Evans, Natalie; Hardon, Anita; Imelda, Johanna; Soyiri, Ireneous; Reidpath, Daniel
Abstract Background Malaysians have become increasingly obese over recent years. The transition from adolescence to early adulthood is recognized as critical for the development of eating and activity habits. However, little obesity-related research focuses on this life stage. Drawing on data from a health and demographic surveillance site in Malaysia, this article describes obesity and overweight amongst adolescents and young adults in a multi-ethnic population. Methods Data were collected at the South East Asia Community Observatory (SEACO) in Segamat District, Johor. In this dynamic cohort of approximately 40, 000 people, 5, 475 were aged 16–35 in 2013–2014. The population consists of Malay, Chinese, Indian and Indigenous (Orang Asli) families in proportions that reflect the national ethnic diversity. Data were collected through health profiles (Body Mass Index [BMI] measurements in homes) and self-report questionnaires. Results Age and ethnicity were associated with overweight (BMI 25.0–29.9Kg/m2 ) and obesity (BMI ≥ 30Kg/m2 ). The prevalence of overweight was 12.8 % at ages 16–20 and 28.4 % at ages 31–35; obesity was 7.9 % and 20.9 % at the same age groups. The main ethnic groups also showed varied patterns of obesity and overweight at the different age groups with Chinese at lowest and Orang Asli at highest risk. Level of education, employment status, physical activity and frequency of eating out were poorly predictive of overweight and obesity. Conclusion The pattern of overweight and obesity in the 16–35 age group further highlights this as a significant period for changes in health-related behaviours. Further longitudinal research is however needed to confirm the observed pattern and investigate causal factors.